Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
Indonesia's external borrowing spreads increased by more than 1000 bps from mid-2007 to late 2008, before subsiding in recent months. The large increase in spreads prompted questions about whether the spreads adequately reflect the improvements in fundamentals made over the past few years. This Selected Issues paper examines the determinants of Indonesia's spreads, and finds that fundamentals can explain both the level of and the increase in spreads. It uses a cross-country panel regression model of emerging market sovereign spreads to yield valuable insights into the pattern of Indonesia's sovereign spreads.